Role of Palm Oil Vitamin E in Preventing Pre-eclampsia: A Secondary Analysis of a Randomized Clinical Trial Following ISSHP Reclassification - Aminuddin, Nurul Afzan; Sutan, Rosnah; Mahdy, Zaleha Abdullah (Frontiers in Medicine, 2021)
Background: Preeclampsia is a significant cause of maternal and perinatal mortality worldwide. Oxidative stress plays a key role in its pathophysiology, hence antioxidants such as tocotrienol may be preventive against preeclampsia. In 2018, the ISSHP revised the definition of preeclampsia. In accordance with the new definition, we report a secondary data analysis from a clinical trial comparing palm oil vitamin E in the form of tocotrienol-rich fraction (TRF) against placebo, in preventing preeclampsia. Method: A randomized double-blind controlled trial was conducted in 2002-2005 to assess the benefits of TRF in preeclampsia prevention. A total of 299 primigravidae were recruited. The intervention group was supplemented with TRF 100mg daily in super-olein capsules, whereas the placebo group was prescribed super-olein capsules without TRF, beginning from 12-16 gestational weeks until delivery. The primary outcome measure was incidence of preeclampsia. Results: The total incidence of pregnancy induced hypertension (PIH) was 5%, whereas the incidence of preeclampsia was 2.3%. The odds of developing PIH (adjusted OR 0.254; 95% CI: 0.07-0.93; p-value 0.038) and preeclampsia (adjusted OR 0.030; 95% CI: 0.001-0.65; p-value 0.025) were significantly lower in the TRF arm compared to the placebo arm. Conclusion: Antenatal supplementation with palm oil vitamin E in the form of TRF is associated with significant reductions in the incidence of preeclampsia and PIH in a single urban tertiary hospital. Palm oil vitamin E deserves further scrutiny as a potential public health preventive measure against preeclampsia and PIH. Keywords: Preeclampsia prevention, antioxidant, palm oil vitamin E, tocotrienol-rich fraction, pregnancy induced hypertension Abbreviations: TRF tocotrienol-rich fraction